PETROPHYSICAL ANALYSIS AND SEISMIC STRATIGRAPHY INTERPRETATION TO DETERMINE HYDROCARBON RESERVOIR IN TARAKAN BASIN, BUNYU ISLAND WATERS - Daffa Dzakwan Shiddiq; Eleonora Agustine; Tumpal Bernhard Nainggolan; Imam Setiadi; Shaska Zulivandama (Marine Geological Institute of Indonesia, 2021)
Tarakan Basin area of Bunyu Island Waters is known to have hydrocarbon potential with complex geological structures. This study aims to determine reservoir characterization and to obtain prospect of hydrocarbon reservoir zones based on petrophysical and seismic stratigraphy analysis with reference to Well DDS-1 and 2D seismic Line S88. Petrophysical analysis results 3 zones that have potential as hydrocarbon reservoirs. Based on petrophysical quantitative analysis, Zone 1 has values of 52.25% for shale volume, 18.48% for effective porosity, 39.84% for water saturation and 13.03 mD for permeability. Zone 2 has values of 54.66% for shale volume, 10.27% for effective porosity, 40.9% for water saturation and 1.14 mD for permeability. Zone 3 has values of 49.22% for shale volume, 9.33% for effective porosity, 56.33% for water saturation and 0.22 mD for permeability. Out of these three reservoir zones in Well DDS- 1, Zone 1 has the prospect of hydrocarbons which is supported by the net pay value. Based on seismic stratigraphy interpretation, the reservoir zone is correlated to the Tabul Formation, which comprises calcareous clay and limestone.